Dot1l expression predicts adverse postoperative prognosis of patients with clear-cell renal cell carcinoma - Qu, Yang (Oncotarget, 2016)
BACKGROUND: Disruptor of telomeric silencing 1-like (Dot1l), a histone methyltransferase that targets the histone H3 lysine 79 (H3K79), has been reported that its high expression is associated with various cancers, while the association between Dot1l expression and clear-cell renal cell carcinoma (ccRCC) is still unknown. PATIENTS AND METHODS: We retrospectively enrolled 282 patients with ccRCC undergoing nephrectomy from a single institution between 2005 and 2007, with a median follow-up of 99 months. Dot1l expression was evaluated by immunohistochemistry in clinical specimens. We compared the clinical outcomes by Kaplan-Meier survival analyses and assessed the prognostic value of Dot1l expression. Harrell's concordance index (C-index) was used to assess the predictive accuracy of different prognostic models. RESULTS: Higher Dot1l expression indicated poorer OS (P<0.001) and RFS (P<0.001) in patients with ccRCC. Moreover, Dot1l expression could stratify ccRCC patients in pT stage, Fuhrman grade and SSIGN/ Leibovich subgroups, which might redefine individual risk stratification. Multivariate analyses further indicated that Dot1l expression was an independent prognostic factor for OS (P=0.007) and RFS (P=0.001). The prognostic accuracy of conventional prognostic models was notably improved with Dot1l integration. Two nomograms and calibration plots were built to predict OS and RFS for patients with ccRCC and performed better based on C-index value. CONCLUSION: Dot1l expression is a promising independent prognostic indicator for postoperative recurrence and survival of patients with ccRCC.